Low Antioxidant Status of Serum Uric Acid, Bilirubin, Albumin, and Creatinine in Patients With Benign Paroxysmal Positional Vertigo - Xie, Ke-Hang; Liu, Ling-Ling; Su, Chu-Yin; Huang, Xiao-Feng; Wu, Bao-Xing; Liu, Run-Ni; Li, Hua; Chen, Qing-Qing; He, Jia-Sheng; Ruan, Yong-Kun (Frontiers in Neurology, 2020)
Objective: Serum uric acid (UA), bilirubin, albumin and creatinine are the major intravascular antioxidant, but their role in benign paroxysmal positional vertigo (BPPV) is unknown. In this study, we have sought to investigate the antioxidant status of serum UA, bilirubin, albumin and creatinine levels in patients with BPPV. Methods: The serum antioxidant status of serum UA, bilirubin, albumin and creatinine were retrospectively analyzed in 70 patients with new-onset idiopathic BPPV and 140 age-and gender-matched healthy controls (HC) in the same period. Results: Serum UA, bilirubin, albumin and creatinine levels in patients with BPPV were significantly lower than the HC. Further, serum levels of bilirubin and albumin in BPPV patients were significantly lower than the HC when separately compared by gender. Multiple stepwise logistic regression revealed that reduced levels of albumin was independently related to BPPV, with odds ratio (OR) 0.688 (95% CI 0.607-0.780). Receiver operating characteristic analyses showed a cutoff value of 45.15 g/L for albumin level with a sensitivity of 74.29% (62.97%–83.07%) and a specificity of 73.57% (65.71%–80.18%). Conclusions: Our study demonstrated that serum levels of UA, bilirubin, albumin, and creatinine were lower in BPPV patients, indicating low antioxidant status in the BPPV patients. Further, reduced levels of albumin was independently associated with BPPV. The study provide insights into the possible roles of oxidative stress ,which was involved in the pathogenesis of BPPV. Antioxidant therapy, such as albumin supplementation, may benefit patients with BPPV